The Impact of Traineeships on the Employment of the Mentally Ill: The Role of Partial Compliance - Alberto Martini; Enrico Rettore; Gianpaolo Barbetta (Institute of Labor Economics (IZA), 2017)
Lavoro&Psiche is a RCT aimed at increasing employment among severely mentally ill patients, by offering them a structured job-search experience. The key feature of the treatment was the presence of a "job coach" entirely dedicated to support the job search of a small number (12-13) of mentally ill patients. What most often the job coach did was finding the patient a traineeship. If one were to consider only the effect of making the support of the coach available the so-called Intention-To-Treat effect it would be a disappointing statistically non significant 5 percentage point difference in the employment of treatment and control members, in the full post-treatment year. However, the impact of making something available is rarely the primary interest of policy-makers, who would rather know the effect of receiving it. The main difficulty in obtaining unbiased estimates of the latter is that 'who receives what' is no longer solely determined by randomization, but also by post-randomization events and decisions. During the implementation period of Lavoro&Psiche of 2011-12, an unprecedented wave of traineeship opportunities hit those enrolled in the demonstration, both in the experimental and in the control group. The main finding is that, for the subset of the experimental group that was induced by the offer to be involved in a traineeship the chances of having a job in the post-treatment year more than double from the 17% of those who did not do any traineeship to the 34% of those who did, well above the Intention-To-Treat impact estimates.
Keywords: J78; J48; J38; 330; mental illness; RCT; traineeships; ITT; tests for selection bias; placebo tests; instrumental variables